Exponential synchronization for hybrid coupled neural networks with time delays via intermittent feedback controls - N. Yotha (2018)
© 2014 Academic Publications, Ltd. This paper, investigates the exponential synchronization of neural networks with time delays and hybrid coupling composed of constant coupling, time-varying delay coupling and distributed delay coupling. The designed controller ensures the exponential synchronization of hybrid couple delayed neural networks are proposed via intermittence feedback control. Based on the design of the outer-coupling matrices, the inner-coupling matrix matrices, and some free matrices representing the relationships between the system matrices. Some sufficient conditions are established to achieve exponential synchronization by constructing of improved Lyapunov-Krasovskii functionals and Kronecker product properties. The criteria are derived in terms of LMIs which can be solved efficiently by standard convex optimization algorithms. A numerical example and its simulation are given to show the effectiveness of the obtained results.